Public library systems : services & networking : a festschrift presented to Prof. K. Sarada - Sarada, K., 1935-; Ramaiah, L. S. (New Delhi : Ess Ess Publications, 1997)
Festschrift honoring Prof. K. Sarada, b. 1935, former librarian, Andhra University, Visakhapatnam; comprises contributed articles on public libraries in India.
Includes bibliographical references and index.
Keywords: Sarada, K., -- 1935-; Public libraries -- India; Library information networks -- India; Information services -- India